Linda Ronstadt [videorecording (DVD)] : the sound of my voice - Ronstadt, Linda; Ronstadt, Linda; Raitt, Bonnie; Parton, Dolly; Harris, Emmylou; Browne, Jackson; Muldaur, Maria; Henley, Don; Geffen, David, 1943-; Ronstadt, Linda (Kino Lorber, 2019)
Linda Ronstadt has been an icon for more than 50 years. Her extraordinary vocal range and ambition created unforgettable songs across rock, pop, country, folk ballads, American standards, classic Mexican music, and soul. As the most popular female recording artist of the 1970s, Ronstadt filled huge arenas as no one had ever done and produced an astounding eleven platinum albums. Ronstadt was the first artist to top the Pop, Country, and R&B charts simultaneously.